Qualitative analysis of the supervision process and identification of constraints that occur in supervision - Tasrif, Elfi (COUNS-EDU: The International Journal of Counseling and Education, 2020)
The quality of education is largely determined by good school management by supervisors for a better quality of learning, not least in Vocational High Schools. This type of research is qualitative with a case study research design. The main target of this research is supervisors of vocational schools in Padang city. This research is limited to describing qualitatively the supervision process and identifying the constraints that occur in supervision. The data source of this research is from key informants, purposively. Data collection techniques with interview and observation techniques. Data analysis by coding, linking and, interpreting themes. The results of the research are the low professionalism of school supervisors and the low appreciation of the school supervisor profession. The conclusion is that the constraints were basically the result of improper recruitment patterns and were exacerbated by weak control mechanisms.